American Joint Committee on Cancer staging for resected perihilar cholangiocarcinoma: a comparison of the 6th and 7th editions. Issue 12 (29th September 2014) - Groot Koerkamp, Bas; Wiggers, Jimme K.; Allen, Peter J.; Busch, Olivier R. C.; D'Angelica, Michael I.; DeMatteo, Ronald P.; Fong, Yuman; Gonen, Mithat; Gouma, Dirk J.; Kingham, T. Peter; van Gulik, Thomas M.; Jarnagin, William R.
Abstract: Objectives: This study was conducted to evaluate the prognostic value of, respectively, the 6th and 7th editions of the American Joint Committee on Cancer (AJCC) staging system for patients with resected perihilar cholangiocarcinoma (PHC). Methods: Patients who underwent resection of PHC between 1991 and 2012 were identified from prospective databases at two centres. Overall survival was estimated using the Kaplan–Meier method and compared across stage groups with the log‐rank test. The concordance index and Brier score were used to compare the prognostic accuracy of the staging systems. Results: Data for a total of 306 patients were analysed. Staging according to the 7th edition upstaged 63% of patients in comparison with staging by the 6th edition. The log‐rank P ‐value for both staging systems was highly statistically significant ( P < 0.001). Staging according to the 6th edition categorized 93% of patients as having stage I or II disease, whereas staging according to the 7th edition distributed patients more equally across stages. Prognostic accuracy was similar between the staging systems: the concordance index was 0.59 and the Brier score 0.17 for both the 6th and 7th editions. The same prognostic accuracy was achieved using an alternative tumour–node–metastasis (TNM) stage grouping simplified to four rather than six stage groups. Conclusions: The 6th and 7th editions of the AJCC staging system for PHC have similar prognostic accuracy. Other prognostic factors can potentially improve individual patient prognostication.